2007
DOI: 10.5650/jos.56.327
|View full text |Cite
|
Sign up to set email alerts
|

Laundry Detergents: An Overview

Abstract: Nowadays laundry detergents are becoming increasingly popular as they can be metered automatically into the washing machine, impart softness, antistaticness, resiliency to fabrics, mild to eyes and skins and shows good dispersibility in water. Because it is consumed when it is used, the sale of laundry detergent is a rather large business. There are many different kinds or brands of laundry detergent sold, many of them claiming some special qualities as selling points. A Laundry detergent composition is a form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(145 citation statements)
references
References 28 publications
1
142
0
2
Order By: Relevance
“…It can be concluded that some nonionic surfactants with EO have a broad capacity to enhance bactericidal activity. Nonionic surfactants with an alkyl group of C12 and EO adduct number of 5-20 are mainly included in a great number of cleaners for their washing properties 8,11 . It is important to adjust the concentration of these nonionic surfactants within the vicinity of their CMC when used in cleaners with bactericides, such as ADBAC, as the bactericidal effects will be greatly improved.…”
Section: Bactericidal Activity With Aementioning
confidence: 99%
See 1 more Smart Citation
“…It can be concluded that some nonionic surfactants with EO have a broad capacity to enhance bactericidal activity. Nonionic surfactants with an alkyl group of C12 and EO adduct number of 5-20 are mainly included in a great number of cleaners for their washing properties 8,11 . It is important to adjust the concentration of these nonionic surfactants within the vicinity of their CMC when used in cleaners with bactericides, such as ADBAC, as the bactericidal effects will be greatly improved.…”
Section: Bactericidal Activity With Aementioning
confidence: 99%
“…Nonionic surfactants are also included in cleaning products to increase the washing performance 8,9 . Methyl ester ethoxylates MEE are well-known ester type nonionic surfactants that have superior washing performance 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…saponin, tannic acid, JBR 515 -Zn > Cu > Cd JBR 425 -Cd > Zn > Cu The literature data indicate that along with an increasing concentration of surface-active compounds in a washing solution above the CMC, the solubility of organic substances increases proportionally to their concentration, which is linked with their solubilization in micelles (Bajpai et al 2007). In the case of metals, their removal from soil may be due to ionic exchange, precipitation-solubilization or counterions exchange (Doong et al 1998).…”
Section: Effect Of Desorbents Concentration On the Effectiveness Of Mmentioning
confidence: 99%
“…Oxygen bleaches are usually used to bleach household clothing to maintain color. The active ingredients, such as sodium percarbonate PC and hydrogen peroxide, release perhydroxy anions for bleaching 13,14 . Key words: norovirus, calicivirus, bleach, virucidal effect viruses declines in an alkaline pH.…”
Section: Introductionmentioning
confidence: 99%